Control estructural de los carbonatos localizados en el Complejo Máfico-Ultramáfico del Cabo de la Vela y su relación con la placa del Caribe - Lascarro Navarro, Frank David (2023)
The Mafic-Ultramafic Complex of Cabo de la Vela (CMUCV) is in the extreme north of South America to the northeast of Colombia, a tectonically complex area due to the interaction of the Nazca, Caribbean and South American plates. This research seeks to understand the relationship of the Caribbean Plate and carbonates located in the CMUCV. By carrying out 16 structural stations and taking 30 rock samples. The results indicate that the outcropping rocks at Cabo de la Vela are pyroxenites, peridotites, serpentinites and amphibolites cut by multiple veins and veins of carbonates in a main stress regime with a trend of 269.2 to 291.1 and plunge of 0.8 to 5.4. It is concluded that there is a relationship between the tectonics of the Caribbean Plate with the carbonates located in the rocks of the CMUCV evident in the regional and local structures such as faults and veins that control the distribution of carbonates, because they were deposited as filler in opening areas caused by the shear of the rocks, in response to the different dextro-lateral and inverse course efforts generated by the Caribbean and South American plates.